Diagnosis and management of the epilepsies in children: a summary of the partial update of the 2012 NICE epilepsy guideline. Issue 12 (6th October 2012) - Appleton, Richard E; Freeman, Amanda; Cross, J Helen
Abstract : The epilepsies of childhood are a heterogeneous group of disorders with different causes, treatments and outcomes. The choice of anti-epileptic drug is largely determined by its effectiveness in a specific epilepsy syndrome, or seizure type(s) if a syndrome cannot be readily identified, and the drug's safety profile. There are minimal randomised controlled trial data to help inform this decision. In January 2012, the National Institute for Health and Clinical Excellence (NICE) published its partially revised and updated clinical guideline on the pharmacological treatment of the epilepsies in children and adults. This partial update provides additional data and also specific recommendations that improve the evidence base for the use of specific anti-epileptic drugs in treating the epilepsies of childhood.